Estimating Elasticities of E-Cigarette Using a Simulate Demand Procedure: Case of Thailand: การประมาณการค่าความยืดหยุ่นของบุหรี่ไฟฟ้าด้วยวิธีการจำลองขั้นตอนอุปสงค์: กรณีประเทศไทย - Saelim, Aunkung; Bejranonda, Somskaow (Journal of Applied Economics and Management Strategy, 2022)
บทคัดย่อ บุหรี่ไฟฟ้าเริ่มเป็นที่นิยมมากขึ้น หากราคาของบุหรี่ทั่วไปสูงขึ้น อาจเป็นไปได้ว่าบุหรี่ไฟฟ้าสามารถใช้เป็นทางเลือกเพื่อทดแทนบุหรี่ทั่วไปได้ วัตถุประสงค์การวิจัยเพื่อประมาณค่าความยืดหยุ่นของอุปสงค์ต่อราคาของบุหรี่ไฟฟ้า ค่าความยืดหยุ่นไขว้ของบุหรี่ไฟฟ้ากับบุหรี่ทั่วไปและค่าความยืดหยุ่นของอุปสงค์ต่อรายได้ ใช้แบบสอบด้วยการออนไลน์กับผู้ใช้บุหรี่ไฟฟ้า 239 รายในเดือนมิถุนายน พ.ศ.2563 การวัดการตอบสนองของการใช้บุหรี่ไฟฟ้าและบุหรี่ทั่วไปด้วยการเปลี่ยนแปลงราคาและรายได้ด้วยวิธี Consumer Purchase Task (CPT) ผลการศึกษาพบว่า ความยืดหยุ่นของอุปสงค์บุหรี่ไฟฟ้าต่อราคามีค่าความยืดหยุ่นต่ำ ค่าความยืดหยุ่นไขว้ระหว่างบุหรี่ทั่วไปและบุหรี่ไฟฟ้าพบว่ามีค่าเป็นบวก บุหรี่ไฟฟ้าและบุหรี่ทั่วไปเป็นผลิตภัณฑ์ที่ใช้ทดแทนกัน และค่าความยืดหยุ่นของอุปสงค์สำหรับบุหรี่ไฟฟ้าต่อรายได้มีค่าเป็นบวก นั่นคือบุหรี่ไฟฟ้าเป็นสินค้าปกติ หากมีการจัดเก็บภาษีบุหรี่ไฟฟ้า รายได้ภาษีมีความเสถียร ABSTRACT E-cigarette (e-cig) is becoming more popular. If conventional cigarette price is increased, it is possible e-cig could be as an alternative to conventional cigarette. The research objectives are to estimate elasticities of price demand, of cross-price demand between e-cig and conventional cigarette, and of income demand. Questionnaire and online survey were conducted to current e-cig users of 239 cases, at June 2020. The Consumer Purchase Task(CPT)technique was applied to measure quantity demanded changes of e-cig and conventional cigarette with respect to price and income changes. The result showed that the price elasticities of the e-cigarettes were inelastic. The cross-price elasticities of the e-cigarettes and the conventional cigarettes were positive indicating the e-cig and conventional cigarette are substituted product. The income elasticities of e-cigarette were positive, pointing e-cig is normal goods. If the e-cig tax measure will be implemented the tax revenue would be rather stable.